Phytochemistry, Nutritional, and Pharmacological Potential of Citrus Limonum - Qurban, Faiza; Hussain, Shabbir; Waqas, Muhammad; Hadiya Shahzad, Hafiza; Rukhsar, Aqsa; Javed, Atif (Scientific Inquiry and Review, 2024)
The current research aimed to provide an overview of the phytochemical configuration, nutritional value, and therapeutic uses of Citrous Limonum (lemon). Its fruit contains a variety of phytochemicals including citric acid, polyphenols, terpenes, limonene, flavonoids, vitamin C, sugar, pectin, citric acid, malic acid, flavonoids, carotenoids, terpineol, fellander, camhenium, citrain, calcium oxalates, and mucilages. Vitamin C is abundant in citrous fruits, as well as macronutrients (dietary fibre and simple sugar) and micronutrients (copper, magnesium, phosphorus, calcium, potassium, pantothenic acid, riboflavin, vit B6 niacin thiamin, and folate). Lemon oil is composed of 70% limonene and 20% monoterpenes, along with significant amounts of aldehydes, such as citral, alcohols (linalool), and esters (coumarin). Lemon peel contains high concentrations of flavonoids, glycosides, coumarins, steroids (beta, gamma, sitosterol), dietary fibers, carbs, and volatile oils, all of which are necessary for good health and appropriate development. However, citrus fruits are low in calories, salts, and cholesterol. They find uses in herbal remedies due to their antioxidant, antifungal, anti-cholesterol, anticancer, antiulcer, antidiabetic, antibacterial, and anti-inflammatory characteristics. It is also important to mention that the excessive use of lemon may also be associated with some risks, such as the lowering of sperm count.